Learning environment associated with use of mixed mode delivery model among secondary business studies students in Singapore - Koh, N.K.; Fraser, Barry (Springer Netherlands, 2014)
At many teacher education institutes around the world, preservice teachers are empowered to use pedagogical tools and strategies that engage their students. We used a modified version of the Constructivist Learning Environment Survey (CLES) to evaluate the effectiveness of a pedagogical model known as the Mixed Mode Delivery (MMD) model in terms of the CLES’s five scales of personal relevance, uncertainty, critical voice, shared control and negotiation. Comparisons were made between 2,216 secondary school students taught by the preservice teachers in an MMD group and 991 students in a control group in terms of the relative magnitudes of the gap between the actual and preferred learning environment in students’ school classrooms. The findings supported the positive impact of using MMD in terms of students’ perceptions of their classroom environments for all CLES scales.